2002
DOI: 10.1136/bmj.325.7370.938
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of home based care of patients with chronic obstructive pulmonary disease

Abstract: Objectives To evaluate usefulness of limited community based care for patients with chronic obstructive pulmonary disease after discharge from hospital. Design Randomised controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
1
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(208 citation statements)
references
References 17 publications
5
192
1
8
Order By: Relevance
“…42 One trial reported significantly reduced adverse drug events as a consequence of pharmacist counselling of patients following discharge but no change in readmissions. 43 Two trials involving 334 patients with chronic lung disease failed to show any impact of nurse home visits on readmissions, 44,45 in contrast to two trials involving 878 patients with cardiac disease that demonstrated a significant (P < 0.05) one-third decrease in readmissions. 46,47 In a Cochrane review of 33 studies involving 5110 patients, telephone calls initiated by hospital staff to patients shortly after discharge failed to reduce readmissions.…”
Section: Post-discharge Home Visits or Telephonic Follow-upmentioning
confidence: 95%
“…42 One trial reported significantly reduced adverse drug events as a consequence of pharmacist counselling of patients following discharge but no change in readmissions. 43 Two trials involving 334 patients with chronic lung disease failed to show any impact of nurse home visits on readmissions, 44,45 in contrast to two trials involving 878 patients with cardiac disease that demonstrated a significant (P < 0.05) one-third decrease in readmissions. 46,47 In a Cochrane review of 33 studies involving 5110 patients, telephone calls initiated by hospital staff to patients shortly after discharge failed to reduce readmissions.…”
Section: Post-discharge Home Visits or Telephonic Follow-upmentioning
confidence: 95%
“…Our findings, however, are consistent with this previous report, and we were unable to identify intervention to reduce 30-day rehospitalizations in patients with COPD exacerbations; our findings also indicate that there do not appear to be interventions that consistently reduce rehospitalizations at subsequent time points (e.g., 6 or 12 months post discharge). Other randomized controlled trials that enrolled ambulatory patients or patients presenting to the emergency department with COPD exacerbations (but not hospitalized) also found inconsistent benefits of interventions designed to reduce hospitalizations (37)(38)(39)(40). Although there appear to be a large number of studies examining strategies to reduce rehospitalizations, the lack of a standard approach to defining patient populations, study interventions and comparators, outcomes, timeframe for assessing outcomes, and settings in which the study was conducted are barriers to cross-study syntheses of evidence.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Alcuni trials clinici randomizzati hanno mostrato che, in pazienti selezionati, l'assistenza domiciliare integrata rappresenta una valida alternativa all'ospedalizzazione per la gestione di una riacutizzazione in assenza di acidosi respiratoria (210)(211)(212)(213).…”
Section: Stabilire Un Piano DI Gestione Della Bpco E Delle Sue Comorbunclassified